Biomedical engineering - Galigekere, Ramesh R.; Ramakrishnan, A.G; Udupa, Jayaram K. (Narosa, 2012)
The papers presented at the International Conference on Biomedical Engineering, conducted under the aegis of the Department of Biomedical Engineering, Manipal Institute of Technology, Manipal University, and the Biomedical Engineering Society of India, brought together in this book bring out the various facets of current biomedical engineering research.